Decreased Functional Connectivity Between the Right Precuneus and Middle Frontal Gyrus Is Related to Attentional Decline Following Acute Sleep Deprivation - Li, Bozhi; Zhang, Liwei; Zhang, Ying; Chen, Yang; Peng, Jiaxi; Shao, Yongcong; Zhang, Xi (Frontiers in Neuroscience, 2020)
Objectives: Acute sleep deprivation seriously affects cognitive functions such as attention, memory, and response inhibition. Previous neuroimaging studies have demonstrated a close relationship between the functional activities of the precuneus and the function of alert attention. However, the specific effect of the precuneus on attention decline after acute sleep deprivation has not been elucidated. In this study, we used resting-state functional magnetic resonance imaging to study the relationship between the changes of the precuneus functional connectivity and alertness decline after total sleep deprivation. Methods: Thirty healthy, right-handed adult men participated in the experiment. Alert attention and functional connectivity were assessed by the Psychomotor Vigilance Test and a resting-state fMRI scan before and after total sleep deprivation. The “ROI to ROI” correlation was employed to analyse the relationship between the precuneus and other brain regions after acute sleep deprivation. Results: Participants showed decreased alert attention after total sleep deprivation. In addition, sleep deprivation induced decreased functional connectivity between the right precuneus and the right middle frontal gyrus. Moreover, there was a significant correlation between the decreased precuneus functional connectivity and alertness decline after total sleep deprivation. Conclusion: Our findings suggest that the interruption of the connection between the right precuneus and the right middle frontal gyrus is related to the observed decline in alert attention after acute sleep deprivation. These results provide evidence further elucidating the cognitive impairment model of sleep deprivation.